Similar biochemical changes associated with multidrug resistance in human breast cancer cells and carcinogen-induced resistance to xenobiotics in rats. - Cowan, K H (1986)
MCF7 human breast cancer cells selected for resistance to doxorubicin (adriamycin; DoxR) have developed the phenotype of multidrug resistance. Multidrug resistance in DoxR MCF7 cells (called AdrR MCF7 cell line in previous publications) is associated with biochemical changes similar to those induced by carcinogens in rat hyperplastic liver nodules (HNs) and associated with resistance to xenobiotics in that system. In HNs and DoxR cells, exposure to a single agent results in the selection of cells that are cross-resistant to a wide variety of structurally dissimilar toxic agents. Resistance in both systems is associated with decreases in intracellular accumulation of toxins and changes in phase I (decreased cytochrome P1-450) and phase II (increased glutathione transferase and glucuronyltransferase) drug-metabolizing activities. In HNs and DoxR cells, resistance is associated with the induction of relatively stable levels of an immunologically related anionic glutathione transferase isozyme (EC 2.5.1.18). The finding of similar biochemical changes associated with the development of resistance to various xenobiotics in HNs and to many naturally occurring antineoplastic agents and at least one carcinogen (benzo[a]pyrene) in DoxR MCF7 cells suggests that the mechanisms of resistance in these two models may be similar.